Improvement of wheat cookies' nutritional quality, by partial substitution with common bean and maize flours, sustained human glycemia and enhanced satiety perception. Issue 5 (26th June 2021) - Mecha, Elsa; Correia, Verónica; Bento da Silva, Andreia; Ferreira, António; Sepodes, Bruno; Figueira, Maria Eduardo; Vaz Patto, Maria Carlota; Rosário Bronze, Maria
Abstract: Background: As a dietetic source of fiber, protein, vitamins, minerals, and phenolic compounds, common beans have potential benefits in human health, namely in chronic diseases' prevention (e.g., cardiovascular diseases and colon cancer). Still, legume consumption, especially in European countries, is below recommendations. The consumers demand for innovative, attractive legume‐based food products suggests a potential future increase in consumption of legumes, especially in modern societies, keen on ready‐to‐eat foods with known health benefits. Objectives: With the aim of studying, the impact of wheat flour's partial substitution by common bean (56%) and maize (22%) flours in the nutritional composition of formulated cookies and its effect on human glycemia and consumers' satiety perception, after ingestion, a human intervention study ( n = 16) was designed. Findings: Approved by consumers, common bean enriched cookies were responsible by reducing glycemic response, and by increasing satiety perception. The nutritional composition of common bean enriched cookies contributed to explain these effects. Conclusions: Common bean enriched bakery food products are valuable nutritional options for consumers concerned with satiety and chronic diseases' prevention. Significance and novelty: This study showed, for the first time, through a human intervention trial the relevance of using legumes (common beans in particular) as alternative ingredients to improve ready‐to‐eat products' nutritional quality.